1994
DOI: 10.3109/13816819409056905
|View full text |Cite
|
Sign up to set email alerts
|

The heritability of strabismus

Abstract: The etiology of strabismus has long been observed to have a genetic component. Recent advances in genetic methodology may provide insight into the genetic basis for several types of inherited strabismus, including those associated with genetic multisystem disorders such as Moebius syndrome, Prader-Willi syndrome, craniofacial dysostoses, and mitochondrial myopathies. Inheritance of primary forms of strabismus, such as congenital ocular fibrosis, Brown syndrome and Duane syndrome, has been reported, but less is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 76 publications
0
41
0
4
Order By: Relevance
“…A higher prevalence of strabismus among families of an affected individual have been demonstrated in several population studies (Ziakas et al 2002). A cohort study of 7100 strabismic patients revealed that about 30 % of the patients had a close relative with strabismus (Paul and Hardage 1994). Cotter et al reported association between positive family history of strabismus and XT, which was independent from hereditability of the refractive error (Cotter et al 2011).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A higher prevalence of strabismus among families of an affected individual have been demonstrated in several population studies (Ziakas et al 2002). A cohort study of 7100 strabismic patients revealed that about 30 % of the patients had a close relative with strabismus (Paul and Hardage 1994). Cotter et al reported association between positive family history of strabismus and XT, which was independent from hereditability of the refractive error (Cotter et al 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Previous twin studies showed a concordance rate of 73 to 82 % among monozygotic twins and 35 to 47 % among dizygotic twins (Paul and Hardage 1994;Matsuo et al 2002). A higher prevalence of strabismus among families of an affected individual have been demonstrated in several population studies (Ziakas et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies have pointed out that at least two types, i.e., congenital esotropia (Francois 1985) and microtropia both show multifactorial inheritance (Maumenee et al 1986;Cantolino & v Noorden 1969) and are caused by multiple and independently inherited sensory and motor anomalies. The mode of inheritance of other forms of strabismus that clusters in families is still somewhat obscure (Paul & Hardage 1994).…”
mentioning
confidence: 99%
“…Studies in Denmark and Finland indicate that the prevalence is greatest at 7 years of age and that the prevalence then is a little less than 5% of the population (Frandsen 1960;Kö hler & Stigmar 1978;Laatikainen & Erkkilä 1980). This should be compared with the prevalence among those with a family history of squint, ranging from 13% to 65% in different studies (Paul & Hardage 1994).…”
mentioning
confidence: 99%